Effect of pharmacological inhibition of P300 on the expression and localization of P53 in triple negative breast cancer - Gallardo, Guillermina Ana (2023)
Triple-negative breast cancer (TNBC) is a heterogeneous group of tumors that lack specific molecular targets. Therefore, it is neces sary to investigate potential tumor markers for this subtype of BC. A relationship between p300 and cancer has been demonstrated; but its role remains unclear, as it has been documented both as a tumor suppressor and an oncoprotein. p300 functions as a transcriptional coactivator, histone acetyltransferase, and acetylates lysines of proteins involved in functions beyond transcription. This protein acts as a transcriptional coactivator of p53, regulating its activity through acetylation mechanisms in various tumor types. Hence, we decided to study whether the regulation of p53 mediated by p300 can influence its cellular localization and the alteration of its functions in TNBC. The aim of this work was to evaluate the effect of pharmacological inhibition of p300 on the expression and localization of p53 in TNBC cell lines (MDA-MB-231 and 4T1). The cell lines were treated with VV59 (an inhibitor of p300 acetylase function) or DMSO (vehicle) for 24 hours. In western blot assays, no significant differences were observed in p53 expression levels in either cell lines. However, a decrease in acetylated p53 levels was noted in the MDA-MB-231 cells treated with VV59 compared to control cells (p=0.0370). Through immunofluorescence, we observed that p300 inhibition reduced nuclear expression and localization of p53 (p<0.0001), accompanied by an increase in cytoplasmic p53 localization, compared to the vehicle, in both cell lines (p<0.0001). In silico assays revealed interaction pathways and high affinity between p300 and p53. These findings suggest that the acetylase function of p300 impacts the expression and localization of p53, providing potential insights into p53 regulation in TNBC cells.